The effect of drip irrigation on the growth of two varieties of sweet corn (Zea mays L.). Issue 1 (1st June 2022) - Muslimah, Y; Lizmah, S F; Harahap, E J; Jasmi,; Alfatah, M
Abstract: This study aims to determine the effect of drip irrigation on the growth of two varieties of sweet corn ( Zea mays L.). This research was conducted in the experimental garden of the Faculty of Agriculture, Teuku Umar University, Meulaboh, West Aceh. The time of the study was carried out on February 19 to May 22, 2021. This study used a separate randomized design (split plot) with the main plot (main plot) of drip irrigation treatment with 2 treatment levels, namely T0 : without drip irrigation and T1 : drip irrigation. Sub plots are sweet corn varieties which consist of 2 treatment levels, namely V1 : bonanza variety and V2 : paragon variety. Parameters observed were plant height, stem diameter, leaf length, number of leaves, leaf width, and leaf color. The results of the F test on the analysis of variance showed that the drip irrigation treatment had no significant effect on all observation parameters except leaf width at 15DAP in the drip irrigation treatment (T1 ). The sweet corn variety used had no significant effect on the observed parameters except for plant height at 15DAP on the bonanza variety (V1 ) and stem diameter at 45DAP on the Paragon variety (V2 ).